High-output heart failure associated with primary plasma cell leukaemia due to arteriovenous shunting: a case report. Issue 9 (7th September 2021) - Sudo, Yuta; Inagaki, Hiroshi
Abstract: Background: Primary plasma cell leukaemia is rarely associated with high-output heart failure, and the underlying mechanism is not well understood. We encountered a rare case of high-output heart failure caused by primary plasma cell leukaemia. Its underlying mechanism was clarified through imaging studies. Case summary: A 49-year-old man with no specific medical history was admitted to our hospital because of heart failure that did not improve with diuretic therapy. His condition was diagnosed as high-output heart failure and primary plasma cell leukaemia after admission. Extensive bone involvement in primary plasma cell leukaemia and arteriovenous shunts in the same lesion were suspected after various imaging studies. The first cycle of chemotherapy with bortezomib, adriamycin, and dexamethasone led to remission of primary plasma cell leukaemia and improved heart failure symptoms. The patient received further chemotherapy in addition to autologous peripheral blood stem cell transplantation and maintenance therapy and had no recurrence of pPCL or heart failure for 1 year to date. Discussion: Primary plasma cell leukaemia can be associated with high-output heart failure, which is caused by arteriovenous shunting at the lesion site with diffuse bone involvement. Imaging studies may lead to the early diagnosis of aetiology and treatment of patients with high-output heart failure associated with primary plasma cell leukaemia.